2019
DOI: 10.1111/ijn.12792
|View full text |Cite
|
Sign up to set email alerts
|

Impact of emotional labour and workplace violence on professional quality of life among clinical nurses

Abstract: Aim: We examined Korean nurses professional quality of life, emotional labour and workplace violence to guide development of interventions to improve nurses professional quality of life. Background: Nurses face heavy exposure to emotional labour and workplace violence. Stress experienced by nurses reduces compassion satisfaction and increases compassion fatigue. Methods: Participants comprised 399 clinical nurses chosen by convenience sampling. Questionnaires measured demographic characteristics, emotional lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…This research demonstrated a significant statistical relation among the severity of the BS, age, and time of professional practice; participants in the age group of 41 or more years and with > 10 years of professional practice have a higher prevalence of medium and high burnout syndrome, these results differ from Mefoh et al, ( 21 ) and Molero-Jurado et al, ( 22 ) who found higher severity of the BS in young individuals who have less protection mechanisms against stress and are more prone to suffering its negative effects. In turn, as described by Roberts et al, ( 23 ) and Kwak et al, ( 24 ) a lower QoPL indicates higher presence of emotional burnout, job dissatisfaction, and high BS.…”
Section: Discussionmentioning
confidence: 75%
“…This research demonstrated a significant statistical relation among the severity of the BS, age, and time of professional practice; participants in the age group of 41 or more years and with > 10 years of professional practice have a higher prevalence of medium and high burnout syndrome, these results differ from Mefoh et al, ( 21 ) and Molero-Jurado et al, ( 22 ) who found higher severity of the BS in young individuals who have less protection mechanisms against stress and are more prone to suffering its negative effects. In turn, as described by Roberts et al, ( 23 ) and Kwak et al, ( 24 ) a lower QoPL indicates higher presence of emotional burnout, job dissatisfaction, and high BS.…”
Section: Discussionmentioning
confidence: 75%
“…Hence, their professionalism and job satisfaction can be improved, and ultimately job burnout and compassion fatigue can be reduced. Moreover, another studies found a strong association between compassion fatigue and poor workplace environment such as patients’ assaults or violence, traumatic events and workplace bullying, which also increased the risk of emotional exhaustion and lack of personal accomplishment(Kim et al, 2019; Kwak et al, 2020; Mangoulia et al, 2015). Consequently, nursing managers should take into account that, to prevent compassion fatigue development among oncology nursing staff, work‐related variables are major factors that cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…All these factors could increase the risk of sleep disturbance. Heavy workload, burnout and workplace violence is common in psychiatric nurses, and these factors are usually associated with lowered QOL (Ibrahim et al, 2016;Kwak et al, 2020). Sleep disturbance may lead to a number of negative outcomes, such as lower job satisfaction (Karagozoglu & Bingol, 2008), emotional disturbance (Lee et al, 2015) and medical errors (Johnson et al, 2014), all of which could further lower QOL (Cimete, Gencalp & Keskin, 2003; Ibrahim et al, 2016).…”
Section: Discussionmentioning
confidence: 99%